2018
DOI: 10.4172/neuropsychiatry.1000225
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zinc in Mood Disorders

Abstract: Mood disorders have many forms, from anxiety attacks, depression, Obsessive Compulsive Disorder (OCD) to Post Traumatic Disorder (PTSD). Recently, many studies have shown that zinc may act as a crucial neuromodulator in glutamatergic and GABAergic balance. What's more, growing evidences considered that zinc be a trait marker of mood disorder. It was reported that zinc deficiency induces depression, while supplementing with this mineral improved mood as well as cognitive function. In this present review, the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…Zinc deficiency results from low food intake and affects growth, immune defense, cognitive function, and bone health. Therefore, zinc deficiency, similar to hypomagnesemia, can increase stress and reduce the quality of life by causing palpitations, dry skin, hair loss, depression, visual disturbance, hearing loss, and loss of taste and smell [35,36]. Our data suggests that beef containing appropriate mineral amounts could offer potential health benefits.…”
Section: Sensory and Mineral Evaluationmentioning
confidence: 83%
“…Zinc deficiency results from low food intake and affects growth, immune defense, cognitive function, and bone health. Therefore, zinc deficiency, similar to hypomagnesemia, can increase stress and reduce the quality of life by causing palpitations, dry skin, hair loss, depression, visual disturbance, hearing loss, and loss of taste and smell [35,36]. Our data suggests that beef containing appropriate mineral amounts could offer potential health benefits.…”
Section: Sensory and Mineral Evaluationmentioning
confidence: 83%
“…A study by Kennedy reported vitamin B6 in the involvement of neurotransmitter pathways; it is a cofactor in the production of serotonin from tryptophan, and that low plasma level of B6 has been associated with depression (Kennedy 2016). Vitamin B-12 has neurological function, and it is also a cofactor in the production of neurotransmitters (Rechenberg and Humphries 2013;Ford et al 2018;Meihua et al 2017). Other functions of B12 include forming red blood cells and maintaining nervous system.…”
Section: Nutritional Science Brain and Mental Healthmentioning
confidence: 99%
“…Other functions of B12 include forming red blood cells and maintaining nervous system. Zinc, is an essential nutritional element which plays many key roles including enzyme catalysis, cell signaling, DNA replication, and transcription and therefore is essential for neural development in learning and memory function as well as mood stability (Meihua et al 2017). Zinc has also been used as an anti-depressant (Ranjbar et al 2013).…”
Section: Nutritional Science Brain and Mental Healthmentioning
confidence: 99%
“…In particular, zinc deficiency can trigger aggressive and antisocialdis position (Piao, Cong, Lu, Feng, Ge , 2017), behavior (attention span, temperament, recreation activities), rough and fine mobility as well as social skills. (Cogia & Sachdev, 2012).…”
Section: Zincmentioning
confidence: 99%